The effect of multi-system relaxation training on reducing stress among judo beginner players - Mohsin Oleiwi, Abbas; Alwan Makttoof, Adnan; Lafta Dakhil, Rabeea (International Journal of Psychosocial Rehabilitation, 2020)
When the judo player is exposed to stressful situations, his nervous activity increases greatly, and the player’s responses are characterized by physical disorders and symptoms such as respiratory disturbance, stomach disorders, increased heart rate and increased excitement more, then the role of relaxation comes as one of the most important strategies to confront and reduce stress, that relaxation is a temporary withdrawal from the activity Absence of tension and tension is allowed, which is stillness and neglect of the senses, and the release of any contraction or tension and reaching zero degrees . The importance of research lays the study of relaxation The sympathetic nervous system responsible for the secretion of adrenaline, high heart rate, and the mind reaching a stage of calm, rest, reassurance and overheating among emerging judo players Polymorphism On Reducing Stress Among Young Judo Hypotheses There are statistically significant differences between the last measurement For me, and the distance in the degree of ability to relax, for the benefit and in the direction of post-measurement among Judo beginners, areas of research, the human field, a sample of Judo wrestlers, Al- Nassiriya club in Thi-Qar , category 16 years, where the number 22 is the temporal player for the time period limited to (1/10/2018) Until (10/5/2019) spatial: Hall of Judo Training Center / Thi-Qar Chapter Three Research Methodology It is the nature of the problem and the goals of the research that determine the appropriate approach to it, so the researcher used the experimental approach to designing the one group in the pre and post method as a reference measurements for comparison The ability to relax scale designed by Frank Vital and prepared his Arabic image Muhammad Hassan Allawi) Always 4, sometimes 3, rarely 2, never 1) taking into account the correct and negative terms The Psychological Stress Symptoms Scale for Athletes consists of (5) dimensions and falls under each dimension (6) phrases to make the number of phrases scale (30) a phrase with a very large degree (4) a medium degree (3) a little degree (2) a little degree (1) a very (There are statistically significant differences between the pre and post measurements in the ability to relax in the judo budge in favor of the post measurement, there are statistically significant differences between the pre and post measurements in the ability to reduce the pressures of the judo budge in favor of the post measurement in the direction of the reduction recommendations, activation implementation of the proposed multi-system relaxation program, as an important psychological skill within the content of the psychological preparation program for national teams and teams and improving the ability to relax from an integrated, comprehensive perspective, the orientation towards studying the effect of multi -syst em relaxation on reducing stress among different samples of athletes, administrators, coaches, and workers in Mathematical environment, to generalize its benefit within the limits of these samples.